The Effects of Earnings Per Share and Firm Size to Stock Price LQ45 Company Listed in Indonesian Securities - Yuliza, Arma (International Journal of Engineering and Technology, 2018)
This study was conducted by the firm that included the stock index of IDX (Indonesian stock exchange) consist of the 45 best stocks (LQ45 index companies) that are listed on the Indonesian Securities. This study aims to assess the effect of earnings per share and the firm size on stock prices. The purpose of this study is also to prove that the size of the firm can moderate the relationship between earnings per share and stock prices. By conducting a regression analysis, this study gives evidence that earnings per share and firm size have a significant effect on stock prices. The size of the firm is also able to moderate the relationship between earnings per share and stock prices. The results of this study gave evidence that profit and the size of the company can provide important information for investors in making decisions.Â